2014
DOI: 10.1093/bja/aeu046
|View full text |Cite
|
Sign up to set email alerts
|

Brain–heart crosstalk: the many faces of stress-related cardiomyopathy syndromes in anaesthesia and intensive care

Abstract: Neurogenic stress cardiomyopathy (NSC) is a well-known syndrome complicating the early phase after an acute brain injury, potentially affecting outcomes. This article is a review of recent data on the putative role of localization and lateralization of brain lesions in NSC, cardiac innervation abnormalities, and new polymorphisms and other genetic causes of the sympathetic nervous system over-activity. Concerns regarding the management of stress-related cardiomyopathy syndromes during the perioperative period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 117 publications
2
74
0
Order By: Relevance
“…Granted, most authors consider their use as harmful. 5,38,52 Recent data from the International Takotsubo Registry indicated that use of catecholamines was a strong and independent predictor of in-hospital death (OR = 9.7) and confirmed that catecholamines should be administered with great caution. 50 On the other hand, numerous case reports indicate hemodynamic improvement and full recovery of ventricular function despite use of vigorous inotropic support.…”
Section: Managementmentioning
confidence: 95%
See 1 more Smart Citation
“…Granted, most authors consider their use as harmful. 5,38,52 Recent data from the International Takotsubo Registry indicated that use of catecholamines was a strong and independent predictor of in-hospital death (OR = 9.7) and confirmed that catecholamines should be administered with great caution. 50 On the other hand, numerous case reports indicate hemodynamic improvement and full recovery of ventricular function despite use of vigorous inotropic support.…”
Section: Managementmentioning
confidence: 95%
“…38,84,186,187 Many have emphasized the importance of avoiding psychological stress in the perioperative period by use of psychological and pharmacologic approaches, including preoperative deep anxiolysis, adequate level of anesthesia during the procedure, optimal postoperative analgesia and sedation, and administration of prophylactic beta-adrenergic blocking agents. If a patient is recovering from an episode of TTCM, it has been advised to delay elective surgery until myocardial wall motion abnormalities return to normal 38,84 and to give preference to regional anesthesia when possible. 186,187 Nevertheless, due to its relative rarity and lack of randomized clinical studies, these are only opinion-based recommendations, and there are inadequate published data for an evidencebased approach to the prevention of any type of TTCM.…”
Section: Perioperative Ttcmmentioning
confidence: 99%
“…Elevated troponin levels were noticed in the first 72 hours likewise [57]. Continuous haemodynamic monitoring with a Swan-Ganz catheter should be considered in order to achieve appropriate measurement of central venous pressure [58]. In case NSC is suspected, a higher level of intensive care management by an interventional neurologist, a neurosurgeon, a cardiologist, and an intensive care practitioner should be carried out.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…While haemodynamic augmentation, described as triple-H therapy (treatment of hypertension, hypervolemia and haemodilution), has been a mainstay in the management of ischaemic cerebral conditions. Fluid balance, β-blockers, inotropes and an intra-aortic balloon pump (IABP) are used for the treatment of NSC after aSAH [52,58]. It is important to optimise cardiac output, maintain euvolemia and avoid hypotension in order to prevent complications including delayed cerebral ischaemia [19].…”
Section: Neurogenic Stress Cardiomyopathy Treatmentmentioning
confidence: 99%
“…I was heartened to see that this approach was echoed quite recently (2014) by Mazzeo et al 11 in their comprehensive review in the British Journal of Anaesthesia. So it may seem paradoxical and perhaps even hypocritical for me to write an editorial about yet more stress cardiomyopathy case reports.…”
mentioning
confidence: 96%